Redefinisi Pendidikan Seni: Analisis Psikopedagogis dan Revitalisasi Kearifan Lokal Minangkabau Di Universitas Negeri Padang - Ega Harna B; Neviyarni S; Herman Nirwana (Kilau Publishing, 2026)
Fine arts education in higher education is often trapped in a dichotomy between industrial demands and bureaucratic formalism, which potentially triggers an